ANALISIS SEMIOTIK RIFFATERRE PADA SYAIR LAGU MAN ANĀ KARYA AL-IMAM AL-HABIB UMAR MUHDHOR BIN ABDURRAHMAN ASSEGAF - Faizetul Ukhrawiyah; Fauziyah Kurniawati (Universitas Sebelas Maret, 2021)
This research aims to elaborate the meaning of message contained in lyrics of song entitled Man Anā by al-Imam al-Habib Umar Muhdhor bin Abdurrahman Assegaf based on semiotic analysis by Michael Riffaterre. This research is descriptive qualitative research. To collect data, researchers use reading and noting technique. Then to analyze data, researchers use Miles and Huberman model. The results of this research reveal that the lyrics of song entitled Man Anā in heuristic reading have scattered meanings and unified ideas. In hermeneutic reading, the potential hypogram produces the meaning of